Crash-testing policies; How scenarios can support climate change policy formulation A methodological guide with case studies from Latin America - Veeger, Marieke; Mason-D'Croz, Daniel; Dunston, Shahnila; Vervoort, Joost M.; Palazzo, Amanda (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The objective of this handbook is to guide policy makers and practitioners from the public, private and research sector in the development and use of scenarios to support the inclusive formulation of policies and other decision-making processes related to complex issues taking place in changing environments. The lessons shared are based on nine policy formulation processes for climate in Latin America supported by the CCAFS future scenarios project since 2013. Five of these cases are discussed to exemplify the steps described to use scenarios and support the development of policies.